Foot health educational interventions for patients and healthcare professionals: A scoping review - Minna Stolt; Heidrun Gattinger; Carina Boström; Riitta Suhonen (Sage, 2022)
Abstract
Objective:
The aim of this scoping review was to examine educational foot health interventions tested with patients and healthcare professionals, with the ultimate goal of improving the quality of foot healthcare by identifying effective educational interventions for foot health.
Design:
Scoping review.
Method:
Three electronic databases (Medline/PubMed, CINAHL and Embase) were searched from citations up to 31 March 2019 within the limits of English language at the title and abstract level to identify foot health interventions. In total, 36 full texts found out of 762 citations were included in the review. Studies were eligible for inclusion if they were empirical, research-based intervention studies in which educational interventions with foot health content were conducted with a sample of adult patients and/or healthcare professionals, and foot health outcomes were reported. Data were analysed by summarising and categorising the studies and interventions. Critical appraisal tools from the Joanna Briggs Institute were used to evaluate the quality of the reviewed studies.
Results:
The educational foot health interventions reviewed were delivered in multiple forms, most often including a lecture, and were conducted individually or in small groups targeting predominantly patients with diabetes. The main content of the interventions was foot self-care. The interventions had positive outcomes for foot health, foot care knowledge, foot care activities and lower limb functional ability.
Conclusion:
This review identified many educational foot health interventions focused mainly on patients with diabetes. All these interventions have the potential to promote foot health in patients, and their future use and development is recommended.